Oryza sativa PULP AS A TEMPLATE IN α-ALUMINA NANOCRYSTALLINE SYNTHESIS BY PRECURSOR CALCINING PROCESS - Rifki Septawendar; Bambang Sunendar Purwasasmita; Suhanda ,; Leanddas Nurdiwijayanto; Taufan Hidayat (Center for Pulp and Paper, 2011)
Synthesis and characterization of α-alumina nano powder with Oryza sativa pulp as template by precursor calcining process have been successfully conducted. The aim of this experiment is to study the potential of Oryza sativa pulp as a template of precursor calcining process method that isrelatively cheaper than that of sol gel method in α-alumina synthesis. Weight ratio between precursor and Oryza sativa pulp was 1 : 2. The effect of calcination temperature on α-alumina synthesis in this research is set by variation of calcination temperature at 900°C, 1000°C, and 1100°C. In this research, X-Ray Diffraction (XRD) analysis is used to investigate the transformation of crystal phase, structure and size of the crystal formed by the calcinations temperature. Scanning Electron Microscope (SEM)characterization is used to identify morphology of α-Al2O3 powder. Based on XRD characterization result, synthesized alumina sample forms α-Al2O3 and γ-Al2O3 crystal phases. The formed crystallite size is in nanometer dimension for α-Al2O3 which biggest crystallite size is 46.6 nm. According to SEM characterization result, it is shown that α-Al2O3 formed rhombohedral or bar shape and planar. The particle size will increase along with the elevation of calcination temperature.Key words : nano powder, α-alumina, precursor calcining process, oryza sativa pulp ABSTRAKSintesis dan karakterisasi nanopowder α-alumina dengan menggunakan pulp merang sebagai template melalui proses kalsinasi prekursor telah berhasil dilakukan. Penelitian ini bertujuan untuk mempelajari potensi pulp merang sebagai template dari precursor calcination process yang merupakan metoda relatif lebih murah dibandingkan metode sol gel dalam mensintesis α-alumina. Perbandingan berat antara prekursor dan pulp adalah 1:2. Pengaruh temperatur kalsinasi terhadap pembentukan α-alumina ditetapkan dengan variasi temperatur kalsinasi pada 900°C, 1000°C, dan 1100°C. Analisis diffraksi Sinar-X (XRD) digunakan untuk mengetahui perubahan fasa kristal, struktur, dan ukuran kristal yangterbentuk pada suhu kalsinasi tersebut. Karakterisasi SEM dilaksanakan untuk mengetahui morfologi dari serbuk α-Al2O3. Berdasarkan karakterisasi XRD, sampel alumina yang disintesis membentuk fasa α-Al2O3 dan γ-Al 2O3. Ukuran kristal yang terbentuk berskala nanometer, yaitu untuk α-Al2O3 ukuran kristal terbesar adalah 46,6 nm. Hasil karakterisasi SEM, terlihat bahwa α-Al2O3 membentuk struktur trigonal atau bentuk batang dan planar, ukuran partikel akan semakin membesar dengan meningkatnyatemperatur kalsinasi.Kata kunci : nano powder, α-alumina, proses kalsinasi prekursor, pulp merang.